2014
DOI: 10.1371/journal.pone.0115898
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drug Release and Pharmacokinetics after Transarterial Chemoembolization Using Diverse Lipiodol Emulsions and Drug-Eluting Beads

Abstract: In many studies for chemoembolization of hepatocellular carcinoma, the Lipiodol emulsion preparation protocols, especially the mixing steps, were unclear or even unrevealed at all. However, doxorubicin (DOX) release may depend on the composition and volume ratio (Lipiodol to DOX solution) of a Lipiodol emulsion. Therefore, we conducted a preclinical study to compare in-vitro drug release and in-vivo pharmacokinetics of DOX from diverse Lipiodol emulsions and drug-eluting beads (DEBs) and to compare the tumor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 27 publications
3
47
0
Order By: Relevance
“…Together with those results, the results of this second part of the study clearly showed that lipiodol alone does not interact directly with DOX membrane transport, and indicate that it is the properties of the complete lipiodol‐based parenteral formulation of DOX that result in its increased tumour‐directed delivery . In fact, it has been demonstrated in other studies that the properties of the formulation may be important for the delivery of DOX to the tumour in vivo . Lipid transport in the body is dependent on lipoproteins, fatty acid binding proteins, lipid transporters (such as ABC transporters), endocytosis and lymphatic drainage .…”
Section: Discussionsupporting
confidence: 59%
“…Together with those results, the results of this second part of the study clearly showed that lipiodol alone does not interact directly with DOX membrane transport, and indicate that it is the properties of the complete lipiodol‐based parenteral formulation of DOX that result in its increased tumour‐directed delivery . In fact, it has been demonstrated in other studies that the properties of the formulation may be important for the delivery of DOX to the tumour in vivo . Lipid transport in the body is dependent on lipoproteins, fatty acid binding proteins, lipid transporters (such as ABC transporters), endocytosis and lymphatic drainage .…”
Section: Discussionsupporting
confidence: 59%
“…DOX-PLGA MSs, which corresponded to 50 g of the drug, suspended in DW (0.15 ml) was added to a mini GeBA-flex tube (12-14 kDa molecular weight cut-off; Gene BioApplication Ltd., Kfar Hanagide, Israel). The tube was immersed in the release media (PBS; pH 5.5, 6.8, and 7.4) and incubated in a shaking bath (50 rpm) at 37 • C. Aliquots (200 l) of the release media were collected at determined times (3,6,9,24,48, and 72 h), and an equivalent volume of fresh media was added at each time point. The released amounts of DOX were determined by the high performance liquid chromatography (HPLC) method as previously reported [3].…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…The tube was immersed in the release media (PBS; pH 5.5, 6.8, and 7.4) and incubated in a shaking bath (50 rpm) at 37 • C. Aliquots (200 l) of the release media were collected at determined times (3,6,9,24,48, and 72 h), and an equivalent volume of fresh media was added at each time point. The released amounts of DOX were determined by the high performance liquid chromatography (HPLC) method as previously reported [3]. In brief, DOX was quantitatively analyzed by a Waters HPLC system (Waters Co., Milford, MA, USA) equipped with a separation module (Waters e2695), a fluorescence detector (Waters 2475), and a column (reverse-phase, C18, 250 × 4.6 mm, 5 m; Xbridge, Waters Co.).…”
Section: In Vitro Drug Releasementioning
confidence: 99%
See 2 more Smart Citations